2012
DOI: 10.1016/j.asieco.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Bank risk and non-interest income activities in the Indonesian banking industry

Abstract: The recent trend of product diversification in the Indonesian banking industry underscores the importance of non-interest income activities. This study examines the relationship between product diversification and bank risk over the period of 2002-2008. Our analysis shows clear evidence that the effect of product diversification on bank risk depends highly on the bank's asset size. Specifically, the degree of product diversification is negatively associated with bank risk for small-sized banks. Conversely, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 10 publications
6
47
3
7
Order By: Relevance
“…According to Baele et al, the diversification gains and costs are not significant for small and large banks in the European Union [15]. Hidayat et al [16] studied the relationship between risk and diversification in Indonesian banks, and the results showed that the effect highly depends on the scale of the bank.…”
Section: The Income Diversification Of Banksmentioning
confidence: 99%
“…According to Baele et al, the diversification gains and costs are not significant for small and large banks in the European Union [15]. Hidayat et al [16] studied the relationship between risk and diversification in Indonesian banks, and the results showed that the effect highly depends on the scale of the bank.…”
Section: The Income Diversification Of Banksmentioning
confidence: 99%
“…Non-interest Income, Profit, and Risk Efficiencies mission and fee income does not have a significant impact on profit efficiency, it has a negative and significant effect on risk efficiency, suggesting that for commercial banks in China, business that generates commission and fee income increases risk. In former studies, DeYoung and Roland (2001), DeYoung and Rice (2004), Stiroh and Rumble (2006), Hidayat et al (2012), andPennathur et al (2012) also find an inverse relationship between non-interest income and risk.…”
Section: Determinants Of Profit and Risk Efficienciesmentioning
confidence: 99%
“…Few papers examine the relationship among non-interest income, profit, and risk in developing countries. Hidayat et al (2012) show that in Indonesia, greater reliance on non-interest income increases risk for small-sized banks but reduces risk for large-sized banks. In addition, commission and fee activities could intensify risk, but the effect of engaging in trading income on risk is less distinct.…”
mentioning
confidence: 99%
“…In addition, Hirtle and Stiroh [39] argue that a stronger focus on retail banking can reduce equity market volatility only for the large banks but not for small and medium banks. Conversely, Hidayat, Kakinaka and Miyamoto [40] suggest that in Indonesia, since the larger banks tend to involve more boldly in non-traditional income activities, which make them become more vulnerable to the volatility of net non interest income, product diversification has an association with bank probability of failure positively for large-sized banks but negatively for smallsized ones. Chen and Lai [41] argue that in case of Taiwan, there is a significant positive short-run relationship between income diversification and bank credit risk due to the earnings fluctuation; nevertheless, in the long run, the effect is reversed when the bank achieves a certain rise in income sources in order to enhance their liquidity reserve ratio and to minify the EPS fragility.…”
Section: A Revenue Diversification and Financial Fragility Of Banksmentioning
confidence: 99%